Functional Gait Assessment to Predict the Risk of Falls in Elderly - Saktivi Harkitasari; Cokorda Agung Wahyu Purnamasidhi; RA Tuty Kuswardhani (WMJ (Warmadewa Medical Journal), 2018)
Aging process represents the natural process which is inevitable. It is caused by a biological factor that goes naturally resulting in the anatomical, biochemical and physiological changes. The natural changes contribute to falling in elderly. The objective of this study was to assess the falling prediction in elderly by using Functional Gait Assessment. This study used a cross-sectional research design with falling prediction as the variable. Forty-three elderly in Panti Werdha Wana Seraya (aged 60-103 years, - mean of 77.48 Â± 1.61), selected according to the inclusion criteria, were included in the study. The data were collected using Functional Gait Assessment and analyzed both descriptively and statistically. The results showed that the elderly had a high risk of falls. Functional Gait Assessment showed that 41 of 43 subjects scored